Meta-analysis of aberrant post-error slowing in substance use disorder: Implications for behavioral adaptation and self-control - Sullivan, Ryan M. (Eur J Neurosci, 2018)
Individual with substance use disorders have well-recognized impairments in cognitive control, including in behavioral adaptation after mistakes. One way in which this impairment manifests is via diminished post-error slowing, the increase in reaction time following a task-related error that is posited to reflect cautionary or corrective behavior. Yet, in the substance use disorder literature, findings with regard to post-error slowing have been inconsistent, and thus could benefit from quantitative integration. Here, we conducted a meta-analysis of case-control studies examining post-error slowing in addiction. Twelve studies with 15 unique comparisons were identified, comprising 567 substance users and 384 healthy controls across three broad types of inhibitory control paradigms (go-no/go, conflict resolution, and stop signal tasks, respectively). Results of the random-effects meta-analysis revealed a moderate group difference across all studies (Cohen’s d=0.31), such that the individuals with substance use disorder had diminished post-error slowing compared with controls. Despite this omnibus effect, there was also large variability in the magnitude of the effects, explained in part by differences between studies in task complexity. These findings suggest that post-error slowing may serve as a promising and easy-to-implement measure of cognitive control impairment in substance use disorder, with potential links to aberrant brain function in cognitive control areas such as the anterior cingulate cortex.